2018
DOI: 10.1111/aen.12328
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem service of biological pest control in Australia: the role of non‐crop habitats within landscapes

Abstract: Semi‐natural areas surrounding field crops are generally shown to enhance natural enemies of pests and biocontrol services within field crops worldwide. However, most of the evidence comes from work conducted in temperate regions of the northern hemisphere and it remains unclear to what extent these conclusions hold true in other parts of the world. Here, we provide an overview of the research in Australia investigating the link between populations of pests and their natural enemies and the type, quality, quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 113 publications
0
40
0
Order By: Relevance
“…However, other factors, not tested in this study, such as the amount or condition of semi‐natural vegetation (e.g. grazing, weediness, structural complexity) might have a positive effect on canopy predation and could also explain some variation in the effects of semi‐natural area on ground predation (Gagic et al, ). Furthermore, ground predation recovered slowly after spraying, while canopy predation remained low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other factors, not tested in this study, such as the amount or condition of semi‐natural vegetation (e.g. grazing, weediness, structural complexity) might have a positive effect on canopy predation and could also explain some variation in the effects of semi‐natural area on ground predation (Gagic et al, ). Furthermore, ground predation recovered slowly after spraying, while canopy predation remained low.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the effects of presence/absence of semi‐natural crop margins, rather than the amount of semi‐natural area in the wider landscape. This is because a recent literature review suggested the larger importance of semi‐natural margins for natural enemies of pests in Australian crops, while responses to landscape composition were inconsistent (Gagic et al, ). Additionally, preliminary analysis showed no effect of the landscape composition (percentage of semi‐natural area) on biocontrol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gagic et al (2018) and Cividanes et al (2018) stressed the importance of native vegetation in agricultural landscapesremnant vegetation supports mostly native beneficial insects, including predators and parasitoids, which provide free ecosystem services across different crops in agricultural systems. For instance, to mitigate the effects of the main threats in Europe and North America, Sánchez-Bayo and Wyckhuysb (2019) recommended a substantial reduction in rates of habitat loss and/or deterioration from land clearing, and drastic changes to contemporary farming practices, especially a significant reduction in the use of pesticides and the wider adoption of integrated pest management.…”
Section: Temporal Replication Of Surveysmentioning
confidence: 99%
“…They are all narrow-range endemics, half of which occurred on islands, which have been impacted by a range of anthropogenic processes, most notably habitat loss, deterioration of habitat quality and invasive species. Essentially, they exemplify the key threatening processes for insects and allied invertebrates summarised in a recent symposium on insect conservation in Australia (Taylor 2018;Taylor et al 2018;Sands 2018;Braby 2018;New 2018;Gagic et al 2018;Carlile et al 2018). However, it is clear from the scientific literature that there are countless cases of documented invertebrate extinctions of species that simply have not been formally listed under any of the state/territory, national (EPBC Act 1999) or international (IUCN Red List of Threatened Species) conservation schedules.…”
Section: Rate Of Extinctionmentioning
confidence: 99%